Human saliva as a source of biochemical genetic markers I. techniques. - Tan, Soon Guan; Teng, Yao Sheng (Karger, 1979)
The number of genetic markers identified in human saliva is still small compared to known genetic markers of blood. Enzyme activities that can be detected in human saliva by spectrophotometric techniques are listed. The methodologies currently available for the detection of biochemical genetic markers by polyacrylamide-gel electrophoresis are summarized.